VD_FINDINFO HC / 2014 / 766 vom 5. Januar 2015 - VD Tribunal cantonal (2015)
RÉSILIATION ABUSIVE, TORT MORAL, CONGÉ DE REPRÉSAILLES | 328 CO, 336 al. 1 let. d CO, 336 CO, 336a al. 1 CO, 336a CO, 49 CO